The influence of big data, content marketing, and artificial neural networks on purchase decisions: the moderating role of purchase intentions - Sudarsono Sudarsono; Azis Rachman (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
This study aims to explore the direct effect of big data variables, content marketing and artificial neural networks on purchase intention variables and purchasing decisions; and 2) the indirect effect of big data variables, content marketing and artificial neural networks on purchasing decisions moderated by purchase interest variables. The method in this study uses a quantitative approach and sampling techniques with simple random sampling, data distributed by google form and offline conducted January - March 2024, a total of 385 data collected. These findings were analyzed with Structural Equation Modeling (SEM) software in the Smart PLS (Partial Least Square) application with indirect and direct. The results showed that directly, big data has a negative but significant effect on purchase intention. Content marketing, directly on purchase intention or purchase decision, has a positive but insignificant effect. And directly, artificial neural networks have a negative but significant effect on purchasing decisions.